Ability of a 9-Item Well-Being Index to Identify Distress and Stratify Quality of Life in US Workers. Issue 8 (August 2016) - Dyrbye, Liselotte N.; Satele, Daniel; Shanafelt, Tait
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To determine whether the well-being index (WBI) can identify US workers in distress and stratify quality of life (QOL). Methods: We used data from 5392 US workers and 6880 physicians to evaluate the efficacy of the WBI and an expanded version of the WBI (eWBI) to identify individuals with distress (high fatigue, burnout, low QOL, and suicidal ideation) and high QOL. Results: Individuals with distress were more likely to endorse each of the WBI items as well as a greater number of total items (all P  < 0.001). The eWBI improved stratification among individuals with low scores and also identified individuals with high QOL in both samples. Conclusions: The eWBI appears to be a useful screening tool to identify individuals in distress across a variety of domains and identify individuals with high well-being.